1991
DOI: 10.1007/bf01275669
|View full text |Cite
|
Sign up to set email alerts
|

On the second eigenvalue and random walks in randomd-regular graphs

Abstract: The main goal of this paper is to estimate the magnitude of the second largest eigenvalue in absolute value, A2, of (the adjacency matrix of) a random d-regular graph, G. In order to do so, we study the probability that a random walk on a random graph returns to its originating vertex at the k-th step, for various values of k. Our main theorem about eigenvalues is thatfor any m < 2[logn L2dv/~g~-l/2J/logdJ, where E denotes the expected value over a certain probability space of 2d-regular graphs. It follows, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
284
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(287 citation statements)
references
References 8 publications
3
284
0
Order By: Relevance
“…Say that X is ν-weakly Ramanujan if Spec(X) ⊂ [−ν, ν] ∪ {−λ 0 , λ 0 } (also we usually insist that ν < λ 0 to prevent a trivial situation). Then building a k-regular graph from k/2 permutations (assuming that k is even), a number of papers have shown that most graphs are ν-weakly Ramanujan (see [BS87,FKS89,Fri91]) for certain values of ν; for example, in [Fri91] it is shown that there is a constant C such that most k-regular graphs on a sufficiently large number of vertices are ν-weakly Ramanujan with ν = 2 √ k + 2 log k + C. Furthermore, numerical experiments (like those in [Fri93]) suggest that most random regular graphs on a large number of vertices are Ramanujan.…”
Section: Introductionmentioning
confidence: 99%
“…Say that X is ν-weakly Ramanujan if Spec(X) ⊂ [−ν, ν] ∪ {−λ 0 , λ 0 } (also we usually insist that ν < λ 0 to prevent a trivial situation). Then building a k-regular graph from k/2 permutations (assuming that k is even), a number of papers have shown that most graphs are ν-weakly Ramanujan (see [BS87,FKS89,Fri91]) for certain values of ν; for example, in [Fri91] it is shown that there is a constant C such that most k-regular graphs on a sufficiently large number of vertices are ν-weakly Ramanujan with ν = 2 √ k + 2 log k + C. Furthermore, numerical experiments (like those in [Fri93]) suggest that most random regular graphs on a large number of vertices are Ramanujan.…”
Section: Introductionmentioning
confidence: 99%
“…The O(d 3/4 ) bound for ρ 2 (G) was improved to O( √ d) by Friedman (using the same model) [50]. A weaker version than Friedman's was obtained independently by Kahn and Szemerédi (cf.…”
mentioning
confidence: 94%
“…A kregular random graph with N nodes is a graph chosen uniformly at random from the set of k-regular graphs with N nodes. In contrast to a normal random graph [11], where node degrees vary, in a k-regular graph, each node's degree is exactly k. For k ≥ 3, a k-regular random graph is almost always a good expander [25], which implies that (i) its diameter grows logarithmically with N [65]; and (ii) it remains connected after random failures of a linear subset of its nodes and/or edges [27]. In addition, such a graph is generally k-connected, i.e., there are k disjoint paths between every two nodes in the graph 2 .…”
Section: Introductionmentioning
confidence: 99%